A general dead-time correction method based on live-time stamping. Application to the measurement of short-lived radionuclides. (December 2017) - Chauvenet, B.; Bobin, C.; Bouchard, J.
Abstract: Dead-time correction formulae are established in the general case of superimposed non-homogeneous Poisson processes. Based on the same principles as conventional live-timed counting, this method exploits the additional information made available using digital signal processing systems, and especially the possibility to store the time stamps of live-time intervals. No approximation needs to be made to obtain those formulae. Estimates of the variances of corrected rates are also presented. This method is applied to the activity measurement of short-lived radionuclides. Highlights: Dead-time correction formulae for superimposed non-homogeneous Poisson processes. Live-timed counting method extended using the time stamps of live-time intervals. Implementation on instruments equipped with digital signal processing systems. Application to the measurement of short-lived radionuclides with background.